Study of the Effect of Gibberellic Acid Urea and Rallis Tracel on the Growth of Teak in the Nursery-I. Enhancement of Growth of Seedling to Transplantable Size in the same Growing Season-a Veritable Possibility - Mehrotra, M. D.; Dadwal, V. S. (Indian Forester, 1978)
The effect of gibberellic acid and nutrients on the growth of teak (Tectona grandis) seedlings in the nursery has been studied. Gibberellic acid when applied alone enhanced height growth of seedlings but at the same time caused ill effects on plant growth. The plants were lanky, chlorotic and developed leaves much reduced in size. The ill effects were more pronounced at 200 ppm than at 100 ppm. However, when the treatment of seedlings with gibberellic acid at 100 ppm was followed by weekly application of urea aad Rallis Tracel, it not only caused reversal of ill effects but alao increased appreciably overall growth of the plants. The plants were vigourously growing and were taller and stouter than the control seedlings. Teak seedlings responded positively to the application of urea The growth of seedlings was considerably enhanced and they developed leaves larger than the control seedllngs. Rallis tracel when applied in combination with urea further increased leaf size and the leaves in this treatment were largest in size. Root-shoot cuttings of the seedlings treated with urea, urea + Rallis Tracel, gibberellic acid at 100 ppm + urea + Rallis tracel and control seedlings when planted in the field showed 100% sprouting in all the cases. Utilization of nursery stock for planting in the same growing season has been emphasized. It is suggested that by early sowing of seed, adequate watering of seedlings during summer months, judicious application of growth hormones and nutrients it may be possible to increase growth of teak seedling. In the nursery to transplantable size by the middle of Jully in the same growing season, instead of middle of August as obtained in the present investigation.